Winning ways for your mathematical plays. - Berlekamp, Elwyn R.; Conway, John H. (John Horton); Guy, Richard K. (Winning ways for your mathematical plays, 2003)
Largely as a result of the ﬁrst edition of "Winning Ways," and of John Conway's "On Numbers and Games," the subject of combinatorial games has burgeoned into a vast area, bringing together artiﬁcial intelligence experts, combinatorists, and computer scientists, as well as practitioners and theoreticians of particular games, games much more interesting to play than the simple examples that we needed to introduce our theory. Just as the subject of combinatorics was slow to be accepted by many "serious" mathematicians, so, even more slowly, is that of combinatorial games. Games are fun to play and it's more fun the better you are at playing them. The subject has become too big for us to do it justice even in the four-volume work that we now oﬀer. So we've contented ourselves with a minimum of necessary changes to the original text (we are proud that our ﬁrst formulations have so well withstood the test of time), with additions to the Extras at the ends of the chapters, and we've corrected some of the one hundred and sixty-three mistakes (1982 edition).